The Auditor's Professional Judgment on Key Audit Matters and Ways to Determine It - Parpiyev Jaxongir Ilxomjonovich (Academia Open, 2025)
General Background: Auditing quality increasingly depends on the robustness of professional judgment, especially in the identification of key audit matters that influence users’ trust in financial information. Specific Background: In Uzbekistan, audit reports frequently present key audit matters in generalized terms, limiting transparency and reducing alignment with ISA 701 standards. Knowledge Gap: Limited empirical evidence exists on how cognitive processes, analytical rigor, and evidence-based assessment shape auditors’ professional judgment in national practice. Aims: This study analyzes how auditors in Uzbekistan develop key audit matters, evaluates the cognitive and methodological criteria they apply, and proposes a structured framework to enhance judgment quality. Results: Empirical analysis of 20 major organizations shows significant variation in judgment quality, with superior performance linked to rigorous risk selection, comprehensive documentation, and strong skepticism, while deficiencies often arise from insufficient transparency and weak analytical depth. Novelty: The study introduces a multi-factor evaluation model combining cognitive appraisal, analytical criteria, and evidence-based assessment to quantify judgment accuracy. Implications: Adoption of systematic decision indicators can reduce subjectivity, enhance consistency across audit practices, increase the credibility of audit reports, and accelerate convergence with international standards in Uzbekistan’s auditing profession.Highlight : Professional judgment determines the depth and credibility of key audit matters. Evidence quality and structured analysis reduce subjectivity in audit conclusions. Cognitive and skeptical approaches strengthen alignment with ISA 701 standards. Keywords : Auditing, Professional Judgment, Important Audit Issues, Cognitive Approach, Evidence